2020
DOI: 10.1002/qute.201900092
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Reconfigurable Mid‐IR Single Photon Sources Based on Functional Ferroelectrics

Abstract: The future of quantum photonic technology depends on the realization of efficient sources of single photons, the ideal carriers of quantum information. Parametric downconversion (PDC) is a promising route to create highly coherent, spectrally pure single photons for quantum photonics using versatile group velocity matching (GVM) and tailored nonlinearities. However, the functionality to actively control the poling period of nonlinear crystals used in PDC is currently missing, yet would enable to dynamically mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
(109 reference statements)
0
12
0
Order By: Relevance
“…Our findings therefore open a new avenue to photonic control of optical devices based on photo-ferroelectric crystals for all-optical modulators, memories and variety of optical logics, possibly extendable even to quantum effects [49] and 2D structures. [50]…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our findings therefore open a new avenue to photonic control of optical devices based on photo-ferroelectric crystals for all-optical modulators, memories and variety of optical logics, possibly extendable even to quantum effects [49] and 2D structures. [50]…”
Section: Discussionmentioning
confidence: 81%
“…The reported optical gating effect can be understood through the competition between light-induced depolarization and a steady photovoltaic effect, which alter the transmission of light through the ferroelectric crystal. Our findings therefore open a new avenue to photonic control of optical devices based on photoferroelectric crystals for all-optical modulators, memories and variety of optical logics, possibly extendable even to quantum effects [49] and 2D structures. [50]…”
Section: Discussionmentioning
confidence: 81%
“…Recently, several works have investigated the generation of entangled photons in MIR range from an SPDC process in the nonlinear crystal. From the theoretical side, in 2016, Lee et al reported a scheme for the generation of polarization-entangled state from periodically poled potassium niobate (PPKN) covering 3.2 to 4.8 µm [8]; In 2018, McCracken et al numerically investigated six novel nonlinear crsystals in order to generate MIR single photons [9]; In 2020, Kundys et al numerically studied the reconfigurable MIR single-photon sources in PMN-0.38PT crystal at 5.6 µm [10]; In 2021, Wei et al theoretically investigated the preparation of MIR spectrally uncorrelated biphotons from an SPDC process using doped lithium niobate (LN) crystals [11];…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Rosenfeld et al experimentally prepared MIR photon pairs in a four-wave mixing process from a silicon-on-insulator waveguide at around 2.1 µm [11]. In 2020 Kundys et al numerically studied the reconfigurable MIR single-photon sources based on functional ferroelectrics, i.e., PMN-0.38PT crystal at 5.6 µm [12]. In the same year, Prabhakar et al experimentally demonstrated the entangled photons generation and Hong-Ou-Mandel interference at 2.1 µm from PPLN crystals [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many biphoton sources have been demonstrated in the previous studies [7,9,10,12,13]; however, from the experimental point of view, it is still lack of high-quality biphotons source at the MIR range, especially the spec-trally uncorrelated biphotons [14][15][16][17][18]. The biphotons generated from an SPDC process are generally spectrally correlated due to the energy and momentum conservation laws.…”
Section: Introductionmentioning
confidence: 99%